2021 9th International Conference on Systems and Control (ICSC) 2021
DOI: 10.1109/icsc50472.2021.9666577
|View full text |Cite
|
Sign up to set email alerts
|

Analytical calculation of inductances under stator inter-turn short circuits fault condition in operating squirrel cage induction motors

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Study of electrical quantities for detection and diagnosis electrical faults like unbalanced supply voltage [4], inter-turn short-circuit faults [8] or a rotor winding problems, is more appropriate and adequate to propose effective fault indicators. However, we notice that mechanical faults have a more particular influence on mechanical quantities which are the same nature [7].…”
Section: Figure 5 Test Benchmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of electrical quantities for detection and diagnosis electrical faults like unbalanced supply voltage [4], inter-turn short-circuit faults [8] or a rotor winding problems, is more appropriate and adequate to propose effective fault indicators. However, we notice that mechanical faults have a more particular influence on mechanical quantities which are the same nature [7].…”
Section: Figure 5 Test Benchmentioning
confidence: 99%
“…A study of asynchronous motor malfunctions has shown that they are classified according to their nature. We distinguish: Bearing faults at 41% [5,6], stator faults at 37% [7,8], rotor faults at 10% [9,10], and other faults at 12% [11,12].…”
Section: Introductionmentioning
confidence: 99%